ANALISIS PERBANDINGAN PERLAKUAN AKUNTANSI ASET BIOLOGIS PADA INDUSTRI PERKEBUNAN (Studi Kasus pada PT Sampoerna Agro Tbk dan PT Dharma Satya Nusantara Tbk) - Amanah, Dian Martha Nurrul; Fitriasari, Riska (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to provide an overview of related variations arising on the disclosure of biological assets by comparing the accounting treatment for biological assets between plantations entities. PT Sampoerna Agro Tbk chosen because it has begun to apply IAS 41 Agriculture, although not fully. This is evident from the statement of management which states that in determining the market price of CPO, the company uses the spot price. Meanwhile, as the entity comparison, PT Dharma Satya Nusantara Tbk selected based on the similarity value of biological assets and corporate performance is not much different. The method used was a descriptive case study. Data were obtained from the annual reports of each entity. Analysis of the data is processed into five aspects: the scope of the report, a description of the biological assets, the recognition and measurement of biological assets, the recognition of fair value, and government grants. The results of this study indicate that the two companies still have not applied the fair value of biological assets as a method of measurement. However, in determining the age of the plant, both of them have a different measurement of plant age which greatly affect the value of the asset. Oriented to IAS 41 Agriculture, the results of this study try to point the public entities, especially plantations entities, to start "learning" apply the fair value. This is intent that in the future can produce accounting information which relevant and reliable.Keywords: Biological Assets, Financial Statement, IAS 41.